2004
DOI: 10.1111/j.0013-9580.2004.41103.x
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Histopathologic Abnormalities and In Vivo Epileptogenicity in the In Utero Radiation Model of Rats Is Dose Dependent

Abstract: Summary:Purpose: Malformations of cortical development (MCDs) are a frequent cause of refractory epilepsy in humans. The in utero radiation model in rats shares many clinical and histopathologic characteristics with human MCDs. Previous studies reported the presence of clinical seizures in radiated rats, but also suggested a dose-dependent differential effect.Methods: Time-pregnant Sprague-Dawley rats were irradiated on embryonic day E17 with 100 cGy (low dose), 145 cGy (medium dose), 175 cGy (high dose), or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 36 publications
5
69
0
Order By: Relevance
“…The convergence of these features in a mouse model could have significant consequences for circuit information processing and/or contribute to the generation of pathological network excitability associated with type I lissencephaly. A number of genetically based animal models of MCD have been developed, and most show robust hyperexcitability and/or spontaneous seizures (Wenzel et al, 2001;Kellinghaus et al 2004;Patel et al, 2004;Kwon et al, 2006;Harrington et al, 2007;Patrylo and Willingham, 2007;Nosten-Bertrand et al, 2008;Greenwood et al, 2009;Kerjan et al, 2009). When synaptic mechanisms have been investigated, these studies have typically reported postsynaptic alterations in glutamatergic excitatory Auerbach et al, 2011;Bateup et al, 2011;Luikart et al, 2011) or GABAergic inhibitory currents (Trotter et al, 2006;Ackman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The convergence of these features in a mouse model could have significant consequences for circuit information processing and/or contribute to the generation of pathological network excitability associated with type I lissencephaly. A number of genetically based animal models of MCD have been developed, and most show robust hyperexcitability and/or spontaneous seizures (Wenzel et al, 2001;Kellinghaus et al 2004;Patel et al, 2004;Kwon et al, 2006;Harrington et al, 2007;Patrylo and Willingham, 2007;Nosten-Bertrand et al, 2008;Greenwood et al, 2009;Kerjan et al, 2009). When synaptic mechanisms have been investigated, these studies have typically reported postsynaptic alterations in glutamatergic excitatory Auerbach et al, 2011;Bateup et al, 2011;Luikart et al, 2011) or GABAergic inhibitory currents (Trotter et al, 2006;Ackman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this decreased inhibition, even in the absence of additional defects, could be sufficient for the generation of seizures, because even small reductions in GABA-mediated function were shown to induce abnormal electrical discharge (Powell et al, 2003;Cobos et al, 2005). Interestingly, a reduction in IPSC frequency was reported in a rodent model of cortical dysplasia (caused by prenatal irradiation) featuring hyperexcitability and rare spontaneous seizures (Zhu and Roper, 2000;Chen and Roper, 2003;Kellinghaus et al, 2004). In both human tissue and experimental models, this reduced IPSC frequency could result from a decreased release of GABA at presynaptic terminals or simply from an impairment of GABAergic terminals and/or cells within the FCD.…”
Section: Reduced Gabaergic Inhibition In Focal Cortical Dysplasiamentioning
confidence: 99%
“…Therefore, in utero irradiation is an injury-based model of diffuse cortical malfomation similar to type I FCD, according to the Palmini classification system (Palmini et al , 2004). Spontaneous seizures have been previously described in these animals (Kellinghaus et al , 2004). …”
Section: Altered Balance Between Excitation and Inhibition In Differementioning
confidence: 83%